The development of a scale to measure concepts of schizophrenia: experience among Brazilian psychiatrists Desenvolvimento de escala para medir conceitos de esquizofrenia: experiência entre psiquiatras brasileiros - Darci N. Santos; Robert Blizard; Anthony H. Mann (Universidade de São Paulo, 1998)
INTRODUCTION: Among psychiatric disorders schizophrenia is often said to be the condition with the most disputed definition.The Bleulerian and Schneiderian approaches have given rise to diagnostic formulations that have varied with time and place. Controversies over the concept of schizophrenia were examined within European/North American settings in the early 1970s but little has since been reported on the views of psychiatrists in developing countries. In Brazil both concepts are referred to in the literature. A scale was developed to measure adherence to Bleulerian and Schneiderian concepts among psychiatrists working in S. Paulo. METHODOLOGY: A self-reported questionnaire comprising seventeen visual analogue-scale statements related to Bleulerian and Schneiderian definitions of Shizophrenia, plus sociodemographic and training characteristics, was distributed to a non-randomised sample of 150 psychiatrists. The two sub-scales were assessed by psychometric methods for internal consistency, sub-scale structure and test-retest reliability. Items selected according to internal consistency were examined by a two-factor model exploratory factor analysis. Intraclass correlation coefficients described the stability of the scale. RESULTS: Replies were received from 117 psychiatrists (mean age 36 (SD 7.9)), 74% of whom were made and 26% female. The Schneiderian scale showed better overall internal consistency than the Bleulerian scale. Intra-class correlation coefficients for test-retest comparisons were between 0.5 and 0.7 for Schneiderian items and 0.2 and 0.7 for Bleulerian items. There was no negative association between Bleulerian and Schneiderian scale scores, suggesting that respondents may hold both concepts. Place of training was significantly associated with the respondent's opinion; disagreement with a Bleulerian standpoint predominated for those trained at the University of S. Paulo. CONCLUSIONS: The less satisfactory reliability for the Bleulerian sub-scale limits confidence in the whole scale but on the other hand this questionnaire contributes to the understanding of the controversy over Bleulerian and Schneiderian models for conceptualisation of schizophrenia, the former requiring more inference and therefore being prone to unreliability. INTRODUÇÃO: Foi desenvolvida uma escala para medir aderência ao conceito Bleuleriano e Schneideriano de esquizofrenia entre psiquiatras trabalhando em São Paulo, analisando relações entre variáveis sociodemográficas e de formação sobre o escore obtido. MÉTODOS: Questionário contendo escala visual analógica com dezessete enunciados sobre conceitos Schneideriano e Bleuleriano de esquizofrenia, foi distribuído para 150 psiquiatras. As sub-escalas Bleuleriana e Schneideriana foram avaliadas por metódos psicométricos de consistência interna, estrutura das subescalas e confiabilidade test- reteste. RESULTADOS: Completaram o questionário 117 psiquiatras. A subescala Schneideriana demonstrou melhor consistência interna e melhores coeficientes de correlação intraclasse. Não houve associação negativa entre os escores das subescalas. Discordância com o conceito Bleuleriano predominou entre profissionais treinados na USP. CONCLUSÕES: A baixa confiabilidade da sub-escala Bleuleriana limita a confiabilidade do instrumento como um todo, embora contribua para a discussão dos modelos em questão. Argumenta-se que o modelo Bleuleriano, por exigir maior inferência, torna-se propenso a baixa confiabilidade.